Manajemen ZIS dalam Peningkatan Perkonomian Masyarakat : (Kajian Perspektif Yusuf Qardhawi pada BAZNAS Kabupaten Bangkalan) - Irdlon Sahil; Luluk Illiyah (Journal of Economic and Islamic Research, 2023)
Poverty in Indonesia is still a problem that is difficult to solve, and poverty continues to increase day by day. In fact, until now we have not yet found the right strategy to become a win solution to minimize the low poverty rate in Indonesia. Moreover, in East Java, namely in Bangkalan Regency, the poverty rate is increasing in 2020. The Bangkalan Regency National Zakat Agency (BAZNAS) in 2019 has realized the distribution of Zakat, Infaq and Alms (ZIS) funds amounting to IDR. 611,295,400 while the funds collected that year amounted to Rp. 887. 417.162. The statement made by the Chairman of the East Java National Zakat Amil Agency stated that Bangkalan Regency has 1.8 billion zakat potential. If this is the case, the percentage of funds realized is 48%. So from this it is necessary to make better efforts than before so that the funds distributed by ZIS to mustahik can be distributed evenly. The aim of this research is to analyze the management of BAZNAS Bangkalan social funds from the perspective of Yusuf Qardhawi. This research uses qualitative methods with case studies to investigate phenomena in real life. The results of this research are that the implementation of zakat, infaq and alms management carried out by BAZNAS Bangkalan Regency is in accordance with Law 23 of 2011 concerning zakat management. In improving the economy of the people of Bangkalan, BAZNAS Bangkalan has done this by providing productive business capital loans for micro business actors who cannot meet their living needs. Yusuf Qardhawi's view regarding the Bangkalan Regency ZIS BAZNAS management analysis has been implemented well and appropriately.